2005
DOI: 10.7863/jum.2005.24.6.805
|View full text |Cite
|
Sign up to set email alerts
|

Second-Trimester Biparietal Diameter/Nasal Bone Length Ratio Is an Independent Predictor of Trisomy 21

Abstract: Objective. The purpose of this study was to evaluate the association between the second-trimester fetal biparietal diameter/nasal bone length (BPD/NBL) ratio and trisomy 21. Methods. Thirty-one cases of trisomy 21 for which complete ultrasound images included the nasal bone were identified from the University of Washington prenatal diagnosis database and matched to 136 euploid fetuses based on maternal age, indication for referral, and gestational age. Results. The mean NBL was shorter (mean ± SD, 2.3 ± 1.7 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
1
21
0
4
Order By: Relevance
“…These studies have shown that some second trimester Down syndrome fetuses do have an apparent absence of the nasal bone whereas others show hypoplasia relative to unaffected fetuses. [2][3][4][5][6][7][8][9] Both the use of MoM and biparietal diameter/ nasal bone ratios seem to provide practical approaches to screening for fetal Down syndrome, because we were unable to demonstrate any significant difference between the two methods. The various studies that have used biparietal diameter/nasal bone ratios have reported widely different sensitivities and specificities for same cutoff (5-7, this study).…”
Section: Discussionmentioning
confidence: 98%
“…These studies have shown that some second trimester Down syndrome fetuses do have an apparent absence of the nasal bone whereas others show hypoplasia relative to unaffected fetuses. [2][3][4][5][6][7][8][9] Both the use of MoM and biparietal diameter/ nasal bone ratios seem to provide practical approaches to screening for fetal Down syndrome, because we were unable to demonstrate any significant difference between the two methods. The various studies that have used biparietal diameter/nasal bone ratios have reported widely different sensitivities and specificities for same cutoff (5-7, this study).…”
Section: Discussionmentioning
confidence: 98%
“…The risk in percent form is easy for the families to understand and interpret. Nuchal fold thickness, 3 nasal bone hypoplasia 4 and mild ventriculomegaly 5 in isolation have a higher risk of aneuploidy compared to other markers in isolation. The relative risk for nuchal fold thickening of >4, >5, >6 mm is 18, 28, 36 respectively.…”
Section: Counselingmentioning
confidence: 96%
“…A total of 136 fetuses were evaluated for the association between the BPD/NBL ratio and trisomy 21 in the second-trimester [19]. In many subsequent studies, assessments of the NBL/BPD ratio were done in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing several past studies, in addition to discussing the relationship between nasal bone length (NBL) and gestational age or biparietal diameter (BPD), the BPD/NBL ratio ≥ 10 and ≥ 11 were proposed for the definitions of nasal bone hypoplasia in the second trimester [13,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%